An Investigation of Chemo‐Mechanical Phenomena and Li Metal Penetration in All‐Solid‐State Lithium Metal Batteries Using In Situ Optical Curvature Measurements. Issue 19 (29th March 2022) - Cho, Jung Hwi; Kim, Kunjoong; Chakravarthy, Srinath; Xiao, Xingcheng; Rupp, Jennifer L. M.; Sheldon, Brian W.
Abstract: Solid‐electrolytes (SEs) can provide a pathway to increase energy‐density in lithium metal batteries. However, lithium metal penetration through garnet based LLZO solid electrolytes has been identified as a critical failure process. This phenomenon is related to chemo‐mechanical processes which are difficult to probe. In particular, characterizing the dynamic mechanical deformations that occur in electrode‐SE structures is very challenging. This study reports in situ curvature measurements that are thus designed to probe chemo‐mechanical phenomena that occur during lithium plating. The novel experimental cell configuration created for this work shows that pressure builds up in the Li metal during plating, up until the point where short circuits occur. The resulting data are analyzed with a detailed finite element model (FEM) to quantitatively evaluate stress evolution. The results show that Li metal plating within a surface flaw can produce stress build‐up prior to short‐circuiting. The combined results from both the experiments and the FEM suggest that it is critical to minimize surface defects and flaws during the manufacturing processes. Abstract : A novel cell design is implemented to accommodate in‐situ curvature measurements during lithium plating through an LLZO solid electrolyte. The measurements show pressure build‐up in the Li metal electrode during plating. Quantitative evaluation using finite element modeling agrees with the experimental measurements, and indicates that lithium plating within a surface flaw can produce significant stress prior to short‐circuiting.